Amidine functionality as a stimulus-responsive building block - Quek, J.; Davis, T.; Lowe, Andrew (2013)
This mini-review describes basic features and applications of small molecules and macromolecules containing amidine, and to a lesser extent, guanidine functional groups. The emphasis in this article is on the exploitation of such functionality as species that are capable of reversibly binding carbon dioxide in the presence of water, a process that also commonly involves a hydrophobic-to-hydrophilic transition. The review is not intended to be exhaustive but rather serves to highlight this one particular feature and demonstrate its application in areas ranging from reversible emulsion stabilization, purification and reversible self-assembly of polymeric nanoparticles.